THE RESULTS OF STUDY OF THE LED LAMP WITH BODY-RADIATOR WITHOUT RIBS: Array - , А. І., Д. О. (Municipal economy of cities. Series: «Economy science», 2018)
The main purpose of this article is to describe the development of a prototype design of an LED luminaire without edges and to compare the lighting characteristics with a sample of a light device, the case-radiator of which is made with ribs. That is why the cooling system of especially powerful LEDs and LED modules is an important part of any lighting device, on which reliability, color and light characteristics depend. The problem of optimizing the thermal regime of lighting devices on the basis of LED light sources by improving the design of the housing-radiator is being solved. The projected development of LED emitters leads to a reduction in the price of LED light sources. This confirms the promising direction of the development of LED light sources and predicts their availability in the wide market in the near future. At the same time, the optimal value of the LED current is maintained at a level close to 700 mA. However, as the current consumed increases, the temperature on the LED also increases, which leads to a decrease in the service life of the LED luminaire. The use of a structure without ribs allows reducing the radiation area without sacrificing the quality of illumination - the amount of luminous flux. Of course, when designing a luminaire, the size of the radiator should be minimized. This requirement is dictated, first of all, by the goals of cost reduction and simplifying the construction. In many cases, the use of a flat radiator is insufficient, therefore, a more accurate calculation may be required before making a layout. The analysis of the basic lighting and electrical characteristics of the samples of the lamp. The results obtained allow us to solve the problem of thermal operation of lighting devices. Keywords: LED, LED lamp, thermal design, body-radiator, ribs.